Valor nutricional do farelo de canola com adição de complexo multienzimático para leitões (15-30Kg) - Lovatto, Francieli Sordi (2016)
The objectives of this study were to determine the nutritional value of canola meal (CM) with the addition of multienzyme complex and evaluate its use in diets for starting piglets (15-30 kg). Two experiments, a digestibility and other performance were carried out. Experiment I, digestibility assays was carried out with 30 barrow pigs of commercial line with initial weight of 15.4 ± 2.32 kg, allotted individually in metabolism cages in experimental design of randomized blocks with six treatments, five replicates and one animal per experimental unit. The treatments consisted of a Reference Diet (RD) with and without addition of multienzyme complex (carbohydrases and protease) and Reference Diet (75%) + Canola Meal (25%) without and with increasing levels (150, 240 and 330 ppm) multienzyme complex. The nutrient digestibility coefficients were calculated to obtain the digestible nutrients that of canola meal. The treatment that showed higher DE (3567 kcal/kg) and ME (3320 kcal/kg) as fed basis for canola meal was the Reference Diet (75%) + Canola Meal (25%) with addition of 240 ppm multienzyme complex. In Experiment II it was used 90 piglets from a commercial line of high genetic potential, half castrated male and half female with 13.89 ± 0.27 kg initial weight and 27.64 ± 0.9 kg final average weight, over experimental randomized block design with four increasing levels of inclusion of CM (7.5, 15, 22.5 and 30%) and adding 240 ppm of multienzyme complex (carbohydrases and protease), nine replicates and two piglets per experimental unit. In addition, a control diet (0% of CM inclusion) and adding 240 ppm of multienzyme complex has been formulated. Regression analysis indicated that there was effect (P≤0,05) of the FC inclusion level on daily feed intake and feed conversion in the starting phase. The results suggest that it is feasible to use up to 20% of canola meal supplemented with multienzymatic complex in diet without impairing performance and PUN of starting piglets. The study of the economic viability indicated that the inclusion of canola meal supplemented with multienzyme complex can reduce the cost of feed, depending on the price relationship between the ingredients.